Romania and Human Rights according to European Regulations - Corsei, Andreea; Ștefănoaia, Mariana-Alina (Acta Universitatis Danubius. Juridica, 2022)
Respect for human rights is for Romania, as well as for the European Union, a priority of foreign policy. According to the Romanian Constitution, Romania is a rule of law, democratic and social state, in which human dignity, citizens' rights and freedoms, free development of human personality, justice and political pluralism are supreme values, in the spirit of the democratic traditions of the Romanian people and the ideals of the December 1989 Revolution and are guaranteed.